Treatment of vulvar cancer recurrences with electrochemotherapy - Vivod, Gregor (Radiology and oncology (Ljubljana), 2023)
Background. Electrochemotherapy has good local effectiveness in the treatment of vulvar cancer. Most studies have reported the safety and effectiveness of electrochemotherapy for palliative treatment of gynecological cancers and mostly vulvar squamous cell carcinoma. Some tumors, however, fail to respond to electrochemotherapy. The biological features/determinants for the nonresponsiveness are not determined yet. Patient and methods. A recurrence of vulvar squamous cell carcinoma was treated by electrochemotherapy using intravenous administration of bleomycin. The treatment was performed by hexagonal electrodes according to standard operating procedures. We analyzed the factors that could determine nonresponsiveness to electrochemotherapy. Results. Based on the presented case of nonresponsive vulvar recurrence to electrochemotherapy, we hypothesize that the vasculature of the tumors prior to treatment may predict the response to electrochemotherapy. The histological analysis showed minimal presence of blood vessels in the tumor. Thus, low perfusion may reduce drug delivery and lead to a lower response rate because of the minor antitumor effectiveness of vascular disruption. In this case, no immune response in the tumor was elicited by electrochemotherapy. Conclusions. In this case, of nonresponsive vulvar recurrence treated by electrochemotherapy, we analyzed possible factors that could predict treatment failure. Based on histological analysis, low vascularization of the tumor was observed, which hampered drug delivery and distribution and resulted in no vascular disrupting action of electrochemotherapy. All these factors could contribute to ineffective treatment with electrochemotherapy.
Keywords: bleomicin; bleomycin; electrochemotherapy; elektrokemoterapija; rak vulve; vulvar cancer